Synthesis and characterization of soluble polyamides from bis-[(4 `-aminobenzyl)-4-benzamide] ether and various diacids - Patil, A. S.; Sayyed, M. M.; Bhairamadgi, Nagendra S.; Han, Sung-Hwan; Maldar, Noormahamad N. (Polymer Bulletin, 2011)
New aromatic diamine containing preformed amide, ether, and methylene; bis-[(4'-aminobenzyl)-4-benzamide] ether (BABE), was synthesized and characterized by FT-IR, NMR, and mass spectrometry. Aromatic-aliphatic polyamides were prepared from BABE with aliphatic/aromatic diacids via Yamazaki's polymerization. The polyamides were characterized by FT-IR, (1)H NMR, inherent viscosity [eta(inh)], solubility tests, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA], and X-ray diffraction [XRD]. Polyamides had inherent viscosities 0.35-0.84 dL/g, soluble in aprotic polar solvents like N-methyl-2-pyrrolidone, N, N-dimethyl acetamide and dimethyl sulphoxide containing LiCl due to an amorphous to partially crystalline morphology; as XRD patterns indicated. DSC analysis of polyamides showed glass transition temperatures 166-268 A degrees C. Polyamides showed high thermal stability as they did not degrade below 300 A degrees C, had 10% weight loss temperature higher than 375 A degrees C, and the char yields at 900 A degrees C were 22-55%; indicating potential applications as engineering materials.
Keywords: Aryl-ether and methylene linkages; Bis-[(4 `-aminobenzyl)-4-benzamide] ether; Direct phosphorylative polycondensation; Soluble aromatic-aliphatic polyamides; Thermal properties